Surgical Considerations for Treatment of Fungal Homograft Endocarditis in Re-re-re-re-do - Peivandi, Armin; Dell'Aquila, Angelo; Kaleschke, Gerrit; Rukosujew, Andreas (The Thoracic and Cardiovascular Surgeon Reports, 2023)
Fungal endocarditis is associated with high surgical mortality rates. Advanced expertise is required for surgical treatment of this serious condition. In the present report, we describe the homograft replacement in a beating heart during re-re-re-re-do in a 29-year-old female patient with fungal endocarditis. The previous operations included Fallot correction at the age of 1 year, Contegra graft implantation in the right ventricular outflow tract (RVOT) due to severe pulmonary insufficiency, homograft implantation in pulmonary position due to Contegra endocarditis, and on-pump pericardial defect closure after homograft injury during sternal rewiring following wound infection.
Keywords: fungal endocarditis; congenital heart surgery; redo; homograft